2016
DOI: 10.1080/19476337.2016.1219391
|View full text |Cite
|
Sign up to set email alerts
|

Botanas expandidas a base de mezclas de harinas de calamar, maíz y papa: efecto de las variables del proceso sobre propiedades fisicoquímicas

Abstract: El calamar gigante (Dosidicus gigas) es de interés comercial como fuente de proteína, y presenta potencial para el desarrollo de productos alimenticios listos para consumir, entre las que se encuentran las botanas expandidas por extrusión (BEE). El objetivo fue determinar el efecto de las condiciones del proceso de extrusión sobre las propiedades fisicoquímicas de BEE elaboradas con 40% de harina de calamar (HC) y 60% de mezclas de harinas de papa (HP)/maíz (HM) en relación (p/ p) 10/50, 30/30 y 50/10. Los mej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Researchers have generated nutritious snacks by incorporating legumes, vegetables or fruits in their formulation (Ding et al ., ; Hagenimana et al ., ). As well as with squid meal, fish powder, tilapia meal and shrimp powder (Jeyakumari et al ., ; Thachil et al ., ; Justen et al ., ; Valenzuela‐Lagarda et al ., ), this has shown that extruded products with acceptable physical properties and competitively commercially can be obtained (Valenzuela‐Lagarda et al ., ). However, the incorporation of edible insect sources to increase the protein content in extruded foods has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have generated nutritious snacks by incorporating legumes, vegetables or fruits in their formulation (Ding et al ., ; Hagenimana et al ., ). As well as with squid meal, fish powder, tilapia meal and shrimp powder (Jeyakumari et al ., ; Thachil et al ., ; Justen et al ., ; Valenzuela‐Lagarda et al ., ), this has shown that extruded products with acceptable physical properties and competitively commercially can be obtained (Valenzuela‐Lagarda et al ., ). However, the incorporation of edible insect sources to increase the protein content in extruded foods has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The sample was fed to a mass flux of 30–40 g/min. The extruded products were exposed to ambient conditions (25C, HR = 65%) and stored in polystyrene bags until use (Valenzuela‐Lagarda et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In Mexico, the giant squid reached a production of 38,300 t. It was sixth by fishing product volume in 2015 (CONAPESCA, ); more than 90% was destined for consumption as a fresh catch, and the rest was consumed as canned goods and dehydrated products (Luna‐Raya, Aragón‐Noriega, & Salinas Zavala, ). Recently, the incorporation of giant squid muscle with starch sources generated expanded extrusion snacks (EES) with acceptable physicochemical properties such as expansion rate (ER), bulk density (BD), firmness, water solubility index, and water absorption index (Valenzuela‐Lagarda et al, ). However, to have a sensory acceptable and commercially competitive EES‐based squid meat, it is necessary to further study the changes in the properties and acceptance of this product.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the giant squid reached the sixth national position (Mexico) in the volume of fishery products [ 3 ]; more than 90% of it was destined for fresh consumption as a source of low-cost protein. Recently, the incorporation of the muscle of the fishing species in extruded products has been evaluated; incorporation of starch is necessary to achieve acceptable physical properties and commercial competitiveness of SEE with animal protein [ 4 ]. During the production of SEE, multiple interactions occur between various ingredients (carbohydrates, proteins and water) that make up the extruded matrix and determine the quality of the product [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that it is possible to prepare snacks based on mixtures of starch with crab [ 8 ], golden fish [ 9 ], red tilapia [ 10 ], shrimp [ 11 ] and fish-squid [ 12 ]; however, generally, these products have a poor expansion capacity (<1.5) due to the high proportions (>30%) of animal protein [ 8 , 11 ]. However, a recent study showed that it is feasible to obtain expanded snacks by extrusion with good expansion, density and texture characteristics from a mixture of squid/potato/corn flours including up to 60% of the squid meal [ 4 ]. Strong interactions between the main macromolecules (protein and starch) present in this extruded matrix can explain this phenomenon and the study of these interactions can significantly impact the development of expanded snacks by extrusion incorporating high levels of various proteins of animal origin in their composition.…”
Section: Introductionmentioning
confidence: 99%